A study of clinical patterns of cutaneous manifestations among hotel workers in costal Karnataka - Bhandary, Pradyumna R.; Kailas, Sanath Posavanike; Kothamasu, Sowmya; Shetty, Supreetha S.; Senapathi, Pradeep (International Journal of Research in Dermatology, 2020)
Background: Catering personnel and other workers exposed to foods may develop both type I and type IV allergic contact dermatitis to foods including spices. Cutaneous manifestations vary according to the place that a worker is employed. Studies on the cutaneous manifestations among restaurant and dhaba workers in India are scarce. This study was conducted to determine clinical patterns of cutaneous manifestations among hotel workers in costal Karnataka. Methods: The present cross-sectional study was carried out among workers of hotels situated in costal Karnataka. Study was conducted through Department of Dermatology, A. J. Institute of Medical Sciences, Mangalore. Consecutive type of non-probability sampling was used for selection of study subjects. A total of 1083 hotel workers from 53 randomly selected hotels, fulfilling eligibility criteria, were included in the study. Results: The prevalence of dermatological manifestations was observed as 34.2% (370/1083) in hotel workers. Prevalence of fungal and bacterial infections was 51.4% and 17.6% respectively. Scabies was found in 6.8% subjects while oral manifestation and nail changes were observed in 3.8% and 2.2% subjects. Conclusion: High prevalence of dermatological manifestations was present in hotel workers especially infective skin conditions like Tinea cruris and scabies. This is important, as they can be a potential source for spread of the infection. There is lot of scope for improving the standards of personal hygiene of hotel workers. Owners of establishments should be made aware of importance of pre-placement and periodical medical examination in order to protect the health of consumer.